Experimental Investigation on the Performance of Cotton Seed Biofuel Blended with Nanoparticles on a Variable Compression Ratio Diesel Engine - P. D. Kabudke (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The rapid increase in worldwide population and changing living style of human are the reasons behind energy crisis. Fossil fuel is a leading factor involved for atmospheric pollutants. However, biofuel play a significant role in increasing engine efficiency and reducing emissions. This research works contributes to enhance the performance of diesel engine. The cotton seed oil is converted into biofuel through transesterification process. Since, raw cotton seed oil, under the category of edible as well as non-edible vegetable oils. The viscosity and calorific value are the distinct properties of biodiesel and diesel fuel. The fuel’s properties, and conducting experiments with compression ratios of 18, 20, and 22. Five constant loads of 0 kilograms, 3 kilograms, 6 kilograms, 9 kilograms, and 12 kilograms are maintained while the engine rotated at a constant speed of 1500 revolutions per minute (rpm) with the injection timing set to 23.5 degrees before the top dead center (TDC) variable. Initial testing was conducted with 18, 20, and 22 compression ratios for CB20, CB30, CB40, and CB100. The BSFC value was 0.34 kg per kilowatt-hour for a mixture of CB20, CR22, and greater BTE. CB20 biofuel with a compression ratio of 22 shows the lowest levels of carbon monoxide, hydrocarbons, and nitrogen oxides